2020
DOI: 10.1002/isd2.12152
|View full text |Cite
|
Sign up to set email alerts
|

Health information systems implementation: Weaving alliances in East African Community

Abstract: This paper addresses the problem of fragmentation and lack of coordination in the context of health information systems. Drawing on a longitudinal action research study of implementing a regional database in East African Community; a process model is developed illustrating forms of institutional work in weaving alliance through three non‐linear phases: standardisation, evolving and stabilisation. The study first contributes by conceptualising weaving alliance as a process whereby novel Information and Communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Consistent with Kooiman (2003) and IS research, the notion of institution that we adopt in this work is that of intermediary agreements and rules that shape corporate and organisational arrangements (North, 1990;Powell & Di Maggio, 1991). The second order is therefore compatible with long standing work in information systems research, which suggests power battles (Bloomfield & Hayes, 2009;Danziger et al, 1982;Kraemer & King, 1986) and institutions (Fountain, 2001;Iannacci, 2010;Sahay et al, 2009;Sarker et al, 2019;Senyoni 2020) mediate digital government transformation, while they tend to explain the mismatch of expectations between set goals and actual results. Following Kooiman's conceptualization of this second order ( 2003) we operationalise this level by addressing the types of interactions between the actors, and the formal and informal rules that steer and guide these actions within organisational and temporal frames.…”
Section: Theoretical Framing Of the Study: Three Orders Of Governance...supporting
confidence: 72%
See 4 more Smart Citations
“…Consistent with Kooiman (2003) and IS research, the notion of institution that we adopt in this work is that of intermediary agreements and rules that shape corporate and organisational arrangements (North, 1990;Powell & Di Maggio, 1991). The second order is therefore compatible with long standing work in information systems research, which suggests power battles (Bloomfield & Hayes, 2009;Danziger et al, 1982;Kraemer & King, 1986) and institutions (Fountain, 2001;Iannacci, 2010;Sahay et al, 2009;Sarker et al, 2019;Senyoni 2020) mediate digital government transformation, while they tend to explain the mismatch of expectations between set goals and actual results. Following Kooiman's conceptualization of this second order ( 2003) we operationalise this level by addressing the types of interactions between the actors, and the formal and informal rules that steer and guide these actions within organisational and temporal frames.…”
Section: Theoretical Framing Of the Study: Three Orders Of Governance...supporting
confidence: 72%
“…Our focused literature review found no studies of HIS in Latin America, which is a limitation to apply the highly contextualised insights of these studies. In addition, HIS contexts are well known for its challenges of coordination of multiple stakeholders in highly fragmented settings (Senyoni, 2020). Unlike HIS, civic technology applications including open government platforms like the one we study, are not characterised by the highly fragmented nature of health systems (Davies et al, 2019).…”
Section: Government Platforms Ecosystem In Ict4d: Collaborative Gover...mentioning
confidence: 99%
See 3 more Smart Citations